2016
DOI: 10.1111/jfpp.13018
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Tomato Pomace Extracts on the Shelf-Life of Modified Atmosphere-Packaged Lamb Meat

Abstract: Tomato production is one of the main industries in Spain and a large amount of by-products, tomato pomace (TP) is generated every year. TP is a promising source of compounds with nutritional, antioxidant and antimicrobial potential. The aim of this work was to study the in vitro antioxidant potential of extracts obtained from TP by using either ethyl acetate (EA) or ethanol (E) solvents, and to evaluate the effect of the addition of extracts by spreading on lamb longissimus thoracis surface in order to improve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
20
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 39 publications
(25 citation statements)
references
References 38 publications
5
20
0
Order By: Relevance
“…The lowest L * and a * value observed in this study was higher than the minimum threshold of acceptability. The current results are in agreement with Andrés et al . and Jiang et al .…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…The lowest L * and a * value observed in this study was higher than the minimum threshold of acceptability. The current results are in agreement with Andrés et al . and Jiang et al .…”
Section: Discussionsupporting
confidence: 94%
“…30 The lowest L * and a * value observed in this study was higher than the minimum threshold of acceptability. The current results are in agreement with Andrés et al 32 and Jiang et al 16 who reported that lycopene had a positive effect on meat discoloration. These changes could be attributed to reduced lipid oxidation.…”
Section: Meat Color Stabilitysupporting
confidence: 93%
“…Tomato by-products are rich in multiple compounds with antioxidant and colourant properties such as carotenes (lycopene, β-carotene, phytoene, phytofluene and lutein), phenolic compounds (phenolic acids and flavonoids), vitamins (ascorbic acid and vitamin A) and glycoalkaloids (tomatine) [13,17,18]. Among them, lycopene is the most important bioactive compound present in the ripened tomato (80-90% of the total pigments) [9].…”
Section: Introductionmentioning
confidence: 99%
“…Storage life can be increased up to a 10-15% by using films with oxygen permeabilities less than 2 cm 3 /m 2 /24 h/bar at 23°C and 0% RH (Š četar et al 2010). Despite the growing number of investigations dealing with packaging of lamb meat in modified atmospheres so far, most of these studies have been focused on lamb cuts and lamb minced meat to this date (Gutiérrez et al 2011;Karabagias et al 2011;Andrés et al 2017). There is scarce scientific literature dealing with lamb forelegs meat, which is highly appreciated for being fleshy and succulent and it is considered a gourmet, delicatessen product for its organoleptic characteristics.…”
Section: Introductionmentioning
confidence: 99%